Pengaruh Pupuk Organik Cair (POC) Terhadap Pertumbuhan Dan Hasil Tiga Varietas Tanaman Selada (Lactuca sativa L.) - Yusuf N, Muhammad; Yusuf, Muhamad (Faculty of Agriculture, Universitas Malikussaleh, 2017)
This study aims to find out organic fertilizers and crops and lettuce products. The study was conducted in Blang Dalam Village Geunteng Nisam District, North Aceh District, from September to November 2017 with a height of 6 meters above sea level. This research will use Randomized Block Design (RAK) Factorial pattern. There are two factors studied, namely: Liquid organic fertilizer (C) consists of 4 levels, namely: C0 = control (without fertilizer), C1 = application of liquid organic fertilizer 4 cc / liter of water, C2 = application of liquid organic fertilizer 8 cc / liter of water, C3 = application of liquid organic fertilizer 12 cc / liter of water. Lettuce varieties (V) consists of 3 levels, namely: V1 = Grand Rapids Varieties, V2 = Lettuce Varieties, V3 = Red Coral Varieties. Thus there were 12 treatment combinations with 3 replications, so there were 36 experimental units. Based on the results of the study showed that: application of liquid organic fertilizer gives a very different effect on growth and yield of lettuce plants and there is a very real interaction